2022
DOI: 10.2147/idr.s341536
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile and Antibiotic Susceptibility Pattern of Neonatal Septicemia and Associated Factors of ICU Hospitalization Days

Abstract: Purpose To evaluate the microorganisms involved in neonatal septicemia and its antibiotic susceptibility pattern and to further investigate the factors associated with the length of intensive care unit (ICU) stay in neonatal septicemia. Patients and Methods A total of 297 infants with septicemia at neonatal ICU (NICU), Maternal and Child Health Hospital of Hubei Province, Tongji Medical College, Huazhong University of Science and Technology from 2016 to 2020 were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
2
2
0
Order By: Relevance
“…This is in accordance with studies conducted by Pooja et al, Kurma et al, Govindaraju et al, and Kamalakannan, which stated that gram-negative rods are the main cause of neonatal sepsis [17], especially Klebsiella pneumoniae [18][19][20]. Contrary to this, Li et al found gram-positive rods as the main cause of neonatal sepsis in their study [21]. The probable reason is that newborns most probably acquire these gram-negative organisms from the maternal genital tract.…”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with studies conducted by Pooja et al, Kurma et al, Govindaraju et al, and Kamalakannan, which stated that gram-negative rods are the main cause of neonatal sepsis [17], especially Klebsiella pneumoniae [18][19][20]. Contrary to this, Li et al found gram-positive rods as the main cause of neonatal sepsis in their study [21]. The probable reason is that newborns most probably acquire these gram-negative organisms from the maternal genital tract.…”
Section: Discussionsupporting
confidence: 90%
“…Our report showed that gram-negative bacteria were the predominant isolated organisms (79.8%) causing neonatal sepsis which was congruent with studies reported from Ethiopia 30% (33) Nigeria78.9% (30), Madagascar 81% (53) and Nepal 69.6% (54). On the contrary, studies in Ethiopia and other countries reported that gram positive bacteria were common cause of neonatal sepsis (23,49), Ghana (31), China (55) and Iran (56).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, gram-positive organisms were most susceptible to vancomycin, imipenem, meropenem, and linezolid, and gram-negative microorganisms were mainly resistant to aminoglycosides and cefotaxime. In Li et al's study, gram-positive bacteria were more sensitive to vancomycin, tigecycline, and linezolid, and E. coli was 100% susceptible to piperacillin, cefotetan, meropenem, and imipenem (20). In the study of Stoll et al, most of the isolated microorganisms showed high sensitivity to ampicillin and gentamicin (16).…”
Section: Discussionmentioning
confidence: 97%
“…However, in the study by Li et (47.17%) was the primary conditional pathogen. Also, E. coli (49.09%) was mainly isolated among gram-negative pathogens (20). Furthermore, Peterside et al reported that gram-positive organisms (53.6%) were more frequent than gram-negative organisms (46.4%).…”
Section: Discussionmentioning
confidence: 99%